Push-Out Bond Strength of Composite Polymerization Methods with Universal Adhesive to Coronal Dentin - Moosavi, Horieh; Rezaei, Fatemeh; Fazli, Mohammad; Rakhshan, Farzaneh (European Journal of General Dentistry, 2021)
Objective This in vitro study was aimed to determine the effect of composite polymerization methods with universal adhesive on push-out bond strength in coronal dentin.Materials and Methods Using 48 healthy premolar teeth, the almost conical access cavities were excised to the canal entry. Cavity preparations were treated with a universal adhesive in the self-etch mode. Teeth were randomly divided into four groups (n = 12). It was used to restore the cavities with a bulk-fill composite; Tetric N-Ceram, a conventional composite; Filtek Z250, a dual-cure composite; Rebilda DC VOCO, and chemical cure composite; Master-Dent. After applying 10,000 thermal cycles, 1-mm incisions were made in coronal dentin, and slices were placed in a UTM machine in a special jig and tested for push-out bond strength at a crosshead speed of 0.5 mm/min. Data were analyzed using one-way analysis of variance and Games–Howell tests (p < 0.05).Results The highest mean bond strength was of the conventional composite (18.36 ± 5.63) and the lowest mean of bond strength was for the dual-cure composite (5.10 ± 2.74). There was a significant difference among the means of bond strength for various composite resins curing (p < 0.001).Conclusion The bulk-fill and conventional light-cured composites had higher bond strength than self- and dual-cured composite resins.
Keywords: push-out; resin composite; universal adhesive